EVALUATING CLINICAL EFFICACY OF KANTAKARI AEROSOL IN THE MANAGEMENT OF BRONCHITIS: A CASE REPORT - Nasreen, *Ahmed; Divya, Kajaria (International Journal of Ayurveda and Pharma Research, 2019)
Bronchitis refers to the inflammation of the bronchi and bronchioles, which helps in the movement of the air through the lungs. Bronchitis can be of two types acute and chronic. Acute bronchitis is very common which mainly occurs due to respiratory infections like common cold and chronic bronchitis on the other hand occurs due to the constant irritation which leads to inflammation of the bronchi mainly due to smoking or environment dust and pollution. Major signs and symptoms are dyspnea, cough with sputum. Main risk factors involves smoking, environmental pollution, dust and recurrent lung infections. In Ayurveda it can be correlated with Tamakashwasa on the basis of similar manifestations. Drug delivery mode through nasal route is termed as inhalation therapy; it has various plus points as compare oral drug administration mode. There is an immediate effect, drug goes directly to the site of pathogenesis and quick abruption of the drug. Rasayana therapy is mainly refers to the attainment of the excellence of body fluids, this helps in the rejuvenation of the body and reduce the recurrence of the disease, it also helps in improving the strength and immunity of the body. A case study was done on bronchitis in the All India Institute of Ayurveda hospital. Inhalation therapy was given for 15 days followed by Rasayana therapy for one month. There was marked improvement in all the signs and symptoms of the disease along with increase in pulmonary function test, also there is no recurrence of the signs and symptoms of the disease after the whole course of treatment during follow up.